2017
DOI: 10.1126/science.aaj2198
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond x-ray spectroscopy of an electrocyclic ring-opening reaction

Abstract: The ultrafast light-activated electrocyclic ring-opening reaction of 1,3-cyclohexadiene is a fundamental prototype of photochemical pericyclic reactions. Generally, these reactions are thought to proceed through an intermediate excited-state minimum (the so-called pericyclic minimum), which leads to isomerization via nonadiabatic relaxation to the ground state of the photoproduct. Here, we used femtosecond (fs) soft x-ray spectroscopy near the carbon K-edge (~284 electron volts) on a tabletop apparatus to dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
331
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(355 citation statements)
references
References 64 publications
9
331
0
Order By: Relevance
“…With the full-valence active space and XMS-CASPT2, the correct state ordering is obtained. Polyak et al observed the ultrafast decay to the ground state (89 ± 9 fs) with large quantum yield (47 ± 8 %) of hexatriene, which was comparable to experimental results (80 to 170 fs lifetime [153][154][155] and 30% to 40% quantum yield). 156 By mapping the distribution of the hopping geometries in the simulations, these lifetime and quantum yields are ascribed to the extended conical intersection seam along the reaction coordinate.…”
Section: B Caspt2 Applicationssupporting
confidence: 69%
“…With the full-valence active space and XMS-CASPT2, the correct state ordering is obtained. Polyak et al observed the ultrafast decay to the ground state (89 ± 9 fs) with large quantum yield (47 ± 8 %) of hexatriene, which was comparable to experimental results (80 to 170 fs lifetime [153][154][155] and 30% to 40% quantum yield). 156 By mapping the distribution of the hopping geometries in the simulations, these lifetime and quantum yields are ascribed to the extended conical intersection seam along the reaction coordinate.…”
Section: B Caspt2 Applicationssupporting
confidence: 69%
“…A temporal resolution of 11 fs is measured in a pump-probe experiment. This duration is already 8/10 enough to consider the observation of ultrafast chemical dynamics at the C K-edge 30,31,52,58 . Improved CEP stability and feedback control over the delay will allow attosecond transient absorption experiments in the SXR in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear from our analysis that it is difficult to disentangle the individual contributions to the total signal, a similar conclusion to the one drawn in a recent paper by Ruckenbauer et al 84 This strengthens the argument in favour of combining data from complementary experimental techniques, 59 which can constrain calculations and inform reduced dimensionality models. The issues associated with overlapping features and spectral congestion are also evident in other examples of global probes such as those based on diffraction 45 or NEXAFS, 58 with both studies using theoretically calculated dynamics to deconvolute and interpret the data. These examples, and the results in this article, support the case for accurate simulations of dynamics, but also demonstrate the need for accurate predictions of how the dynamics projects onto the measurement.…”
Section: Discussionmentioning
confidence: 99%
“…This includes coherent control, both experiment 43,48,49 and theory, 7,50,51 and a range of new ultrafast imaging techniques 52 such as electron diffraction, [53][54][55][56] X-ray scattering, 44,45 Coulomb explosion, 57 and near-edge X-ray absorption fine structure (NEXAFS). 58 The variety of complementary observations generated by these techniques holds great promise for tying down a complete understanding of this important and complex reaction, for instance by combining X-ray scattering and photoelectron data such as in ref. 59.…”
Section: Introductionmentioning
confidence: 99%